Walasuji Tradition in Bugis Tribe Traditional Weddings from an Islamic Law Perspective (Case Study in Solo Village, Bola District) - Abu Haif; Sulfiana Sulfiana; Ilfah Luthfiah; Hendri Hendri; Af Amul Khair (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines the Walasuji tradition, a part of the Bugis traditional wedding procession that still persists today. Walasuji is a rectangular woven basket filled with various fruits and foodstuffs, each with symbolic meaning. Etymologically,